(untitled) (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
The rapid advancement of smart technologies has transformed human interaction, governance, and economic systems, but it has also raised deep ethical and social concerns about privacy and autonomy. Digital surveillance, embedded in everyday devices, social platforms, and state security systems, now operates as an invisible infrastructure of control. This research paper explores how pervasive surveillance challenges human autonomy, data ownership, and the fundamental right to privacy. Through theoretical analysis and case-based evaluation, it investigates the impact of digital surveillance on individuals and societies, the trade-off between security and freedom, and the possibilities for creating ethically governed digital ecosystems.